South African Heart Association newsletter - Authors, Various (SA Heart Journal, 2017)
The surgical group has been busy, very busy, with organising the 2016 congress which will form part of the World Society of Cadiothoracic Surgeons’ 26th annual meeting this year. The meeting will be jointly hosted by SOCTS and SA Heart Association and will run from 8 - 11 September at the Cape Town ICC.